A Systematic Literature Review of Implementation Quality Control Circle in Manufacturing and Services Industries - Indra Maulana Fahturizal (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2020)
A quality control circle (QCC) is a group of workers who do the same or similar work, who meet regularly to identify, analyze, and solve work-related problems. This paper is a literature review on the role of QCC in enhancing work safety in the manufacturing and services industry. This paper explores how quality control circles (QCC) enhance work safety in a firm manufacturing environment. The method used is reviewing inquiry papers that use QCC consistently. The findings of this study can be considered as a roadmap for the successful implementation of QCC in all industries. The results obtained contribute to advances on QCC research for identifying that the concepts sustainable of quality manufacturing and service industries can enable quality to have positive impacts on all the sustainability dimensions in an integrated way, and also supporting the implementation of the quality plan in the following aspects: continues improvement; quality management; management improvement. In essence, these research results will help management make crucial decisions and resource allocations required to make the QCC implementation a succes.